The analysis of e-commerce website features on customer’s purchase intention using fuzzy expert system - Mohd Abdoh, Wan Mohd Yaseer; Mohd Idris, Mohd Fazril Izhar; Abd Aziz, KhairuAzlan; Roslan, Ibrahim (UiTM Cawangan Johor, 2021)
The rapid growth of internet users over the past few decades indicates a changing in the business model, in which previously the business only focuses on brick and-mortar store whereas no" exists a need to add another store named as the e-commerce store. Business-to-Consumer (B2C) e-commerce is one of the various types of e-commerce, which has turned into an influential key to business channel. In order to meet the demands of the current business model, numerous e-commerce websites have been developed. However, building an e-commerce website is not enough if it does not meet the customers' expectation, which influences the customers' purchase intention. This study investigates the features of an e-commerce website that influences the customers' purchase intention as well as the most important feature of an e-commerce website based on the customers ' perspective. The e-commerce, website features that being investigated are, website design, information quality, security and privacy which are gained from the literature review. The data is collected through an online survey which consists of 358 respondents who are familiar with purchasing on the e-commerce website. An expert system has been developed by using a fuzzy logic approach to determine which feature possesses the biggest influence on customers in order to perform purchasing on the e-commerce website. The results performed in the MATLAB software